أثر تدريس مادة العلوم بإستخدام الرسوم الكرتونية البرمجة في تعديل الفهوم الخطاء لدى تلاميذ الصف الرابع الأساسي بأمانة العاصمة = The impact of teaching science using P cartoons on changing misconceptions of fourth graders in the city of Sana’a schools - Albukea, Adel Ali Abdullah; Al-Hidabi, Dawood Abdulmalek Yahya; Alhjami, Ahmed Sultan (2017)
The aim of current research to investigate the impact of teaching science using cartoons to change 4th grade pupils misconceptions in science. The sample consisted of (90) female pupils who were divided into three groups, first experimental group consisted of 30 pupils, who were taught by the teacher using the cartoons software , the second experimental group consisted of 30 pupils , who used cartoons software by the pupils themselves( self-learning).The third group tested (the control group) consisted of 30 pupils where the teacher used the traditional method. The research tool was achievement test to check the change in misconception on animals and plants concepts of fourth grade science units in Sana'a. Pre- and post-test was applied for the three groups. Results showed statistical significant differences between the means of the three groups. In the light of the research findings, a set of recommendations were offered.